Pengaruh Ulasan Produk, Influencer Dan Layanan Cash On Delivery Terhadap Checkout Payment Tiktok Shop Di Kota Malang - Alfi, Ahmad Fauzan; Hidayati, Nur; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The high cart abandonment rate of 73% at TikTok Shop indicates a significant gap between consumer interest and transaction realisation which requires identification of factors that influence checkout payment decisions. This study aims to analyse the influence of product reviews, influencers, and cash on delivery services on TikTok Shop checkout payments in Malang City to provide strategic solutions for optimising sales conversion. This research uses a quantitative approach with an explanatory research design, involving 85 respondents of TikTok Shop users in Malang City through snowball sampling techniques based on the Heir et.al formula. Data analysis was carried out using multiple linear regression analysis techniques with the help of SPSS software. The results showed that product reviews have a significant effect on checkout payments, while influencers and cash on delivery services have no significant effect on checkout payments. This study confirms the importance of product reviews as the most determinant factor in e-commerce conversion, especially on a relatively new platform such as TikTok Shop. The managerial implication of this finding is the need for a strategy that focuses on product and service quality to encourage positive reviews as a key driver of checkout payments. Keywords: Product Reviews, Influencers, Cash on delivery Service, Checkout payment, Tiktok Shop, Online Purchasing Behaviour, Malang City